اﻟﻣﮭﺎرات اﻟﺗدرﯾﺳﯾﺔ ﻟﺗدرﯾس ﻣﺎدة اﻟﺗﺎرﯾﺦ ﻓﻲ اﻟﻣرﺣﻠﺔ اﻟﻣﺗوﺳطﺔ ﻣن وﺟﮭﺔ ﻧظر ﻣدرﯾﺳﯾﮭﺎ (Journal of the College of Education for Women, 2019)
The current study aims at specifying the required teaching skills to teach history in the intermediate stage according to the point of view of history teachers . The Study is applied in Iraq , Baghdad on the schools of the First and Second Rusaffa directory for the academic year of 2008– 2009 . The researcher prepared a tool of study as a questionnaire of 30 items with three options . They are distributed to six fields . The researcher checked the tool's validity by consulting experts in the field of history and educational an psychological sciences .and the factor of validity of the tool of study is derived through depending on initial test of samples of the society of research which is of 30 male and female teachers . The ratio of the validity of the six fields has been about ( 0.66 – 0.93 ) and the average of the validity ratio has been ( 0.97 ) as an accepted ratio in general educational and psychological studies . In order to specify the teaching skills and the importance of its order according to the teachers of history ,the researcher applies the tool of study on a sample of (90 ) female and male teachers between ( 2 – 12 – 2008 to 28 – 12 – 2008 ) with the help of prison factor and the percentage weight and the suggested means to treat the data of the study and the results are : First : in the fields of A –the tool : the six fields of the tool is arranged according to the ratio of the suggested means and the percentage weight descending , therefore , the first was the field of the skills of ( material assessment ) , second was the field of ( presenting the material ) , third was the field of ( teacher training ) fourth was the field of ( the professional growth of the teacher ) , fifth was the field of ( the philosophy and the educational objectives ) , sixth was the field of ( class management ) the values of the suggested means were between ( 2.59 ) and ( 2.22 ) and their percentage weights were between ( 68.54 ) and ( 74.18 ) successively . The general ratio of the suggested means was ( 2.45 ) and the percentage weight was ( 81.80 ) . B – the achieved items : the number of the achieved items of the teaching skills of the sample was ( 24 ) teaching skills of ( 30 ) skills which gave an average of ( 80% ) of the total number with suggested means between ( 2.877 ) and ( 2.044 ) and their percentage weights between ( 95.9 ) and ( 63.13 ) successively . C – The unachieved items : The number of the unachieved items was ( 6 ) skills with an average of ( 20% ) of the total number their suggested means between ( 1.988 ) and ( 1.811 ) and their percentage weights between ( 66.26 ) and ( 60.36 ) successively . Relatively , the researcher put a number of suggestions and recommendations .